Effects of sensory substituted functional training on balance, gait, and functional performance in neurological patient populations: A systematic review and meta-analysis. Issue 9 (September 2021) - Lynch, Peter; Monaghan, Kenneth
Abstract: Introduction: Sensory Substitution (SS) is the use of one sensory modality to supply environmental information normally gathered by another sense while still preserving key functions of the original sense. Objective: This systematic literature review and meta-analysis summarises and synthesise current evidence and data to estimate the effectiveness of SS supplemented training for improving balance, gait and functional performance in neurological patient populations. Methods: A systematic literature search was performed in Cochrane Library, PubMed, Web of Science, and ScienceDirect. Randomized controlled trials (RCTs) using a SS training intervention were included. Results: Nine RCTs were included. Outcome measures/training paradigms were structured according to the balance framework of Shumway-Cook and Woollacott: Static steady-state, Dynamic steady-state and Proactive balance. Meta-analyses revealed significant overall effects of SS training for all three outcomes, as well as self-assessment and functional capacity outcomes, with Dynamic Steady-State balance and ability of stroke survivors to support bodyweight independently on paretic side lower limb found to have had the largest statistical and clinical effects. Meta-analyses also revealed non-significant retention effects. Conclusion: This review provides evidence in favour of a global positive effect of SS training in improving Static steady-state, Dynamic steady-state and Proactive balance measures, as well as measures of self-assessment and functional capacity in neurological patient populations. Retention of effects were not significant at follow-up assessments, although no intervention met training dosage recommendations. It is important for future research to consider variables such as specific patient population, sensor type, and training modalities in order identify the most effective type of training paradigms. Abstract : Sensory Substitution; Neurorehabilitation; Neuroplasticity; Neuropsychology; Balance; Gait; Systematic review; Meta-analysis.